2017
DOI: 10.1021/acs.biomac.7b01502
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Poly(vinyl alcohol)-Mediated Ice Recrystallization Inhibition through Ice Adsorption Measurement and pH Effects

Abstract: The development of improved cryopreservative materials is necessary to enable complete recovery of living cells and tissue after frozen storage. Remarkably, poly(vinyl alcohol) (PVA) displays some of the same cryoprotective properties as many antifreeze proteins found in cold tolerant organisms. In particular, PVA is very effective at halting the Ostwald ripening of ice, a process that mechanically damages cells and tissue. Despite the large practical importance of such a property, the mechanism by which PVA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 48 publications
1
49
0
1
Order By: Relevance
“…The coverslip is placed in heptane, which had been cooled to –80 °C with dry ice, and then transferred to a –6 °C glass box cooled by circulation. After being kept at a constant temperature for 30 to 60 min, the micrographs were recorded (Burkey, Riley, Wang, Hatridge, & Lynd, 2018; Li et al., 2017). This method was transferred at low temperatures, so the operation is understandably difficult.…”
Section: Evaluation Methods Of Antifreeze Activitymentioning
confidence: 99%
“…The coverslip is placed in heptane, which had been cooled to –80 °C with dry ice, and then transferred to a –6 °C glass box cooled by circulation. After being kept at a constant temperature for 30 to 60 min, the micrographs were recorded (Burkey, Riley, Wang, Hatridge, & Lynd, 2018; Li et al., 2017). This method was transferred at low temperatures, so the operation is understandably difficult.…”
Section: Evaluation Methods Of Antifreeze Activitymentioning
confidence: 99%
“…As a result, other researchers have synthesized various polymers and polyampholytes which have been assessed for IRI properties. The TH and IRI activity of various polymers (Figure ) containing poly‐ l ‐histidine 12 , poly‐ l ‐hydroxyproline 13 , poly‐ l ‐lysine 14 , poly‐ l ‐asparagine 15 , polyacrylic acid 16 , polyvinylpyrrolidone 17 , polyethylene glycol 18 , and polyvinyl alcohol 19 have been reported . Similar to the AFGPs, it was observed that larger polymers exhibited increased IRI activity .…”
Section: Alternatives To Natural Af(g)psmentioning
confidence: 69%
“…Contrary to the strong, irreversible adsorp-tion of AFP, the interaction between PVA and ice is weak and reversible. The PVA in solution that adsorbed on ice may be less than 9% [28]. When the concentration of PVA is only 5 × 10 −7 mol/L, it can still effectively inhibit ice recrystallization [29].…”
Section: Polyvinyl Alcohol (Pva)mentioning
confidence: 99%